History of cooperation between Azerbaijan and Georgia in transit and transport projects of Caspian energy resources - Hajiyeva , Khatira (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
One of the main factors influencing the development of bilateral relations and the expansion of regional cooperation was the fact that Azerbaijan has rich energy resources, and Georgia has transit opportunities. Since the 19th century, the export route of Azerbaijani oil has traditionally passed through the Black Sea ports of Georgia to enter foreign markets. The restoration of that export route in modern times was in the strategic interests of both sides. For this reason, the implementation of the proposed regional projects served the well-being of the region. The fact that Azerbaijan plays the role of the main producer and Georgia plays the role of a transit in the energy supply of Europe played an important role in their joint cooperation. Azerbaijan and Georgia played an important role in Europe’s energy security, in the diversification of the energy market, and in the creation of energy infrastructure. Strategic cooperation between them was one of the factors that strengthened their position, not only in the international arena, but also in the entire European continent in terms of energy security.